2020
DOI: 10.1186/s12864-020-06952-w
|View full text |Cite
|
Sign up to set email alerts
|

A tentacle for every occasion: comparing the hunting tentacles and sweeper tentacles, used for territorial competition, in the coral Galaxea fascicularis

Abstract: Background Coral reefs are among the most diverse, complex and densely populated marine ecosystems. To survive, morphologically simple and sessile cnidarians have developed mechanisms to catch prey, deter predators and compete with adjacent corals for space, yet the mechanisms underlying these functions are largely unknown. Here, we characterize the histology, toxic activity and gene expression patterns in two different types of tentacles from the scleractinian coral Galaxea fascilcu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 96 publications
(131 reference statements)
0
13
0
Order By: Relevance
“…Another working hypothesis is that these candidate toxins could reach the competitor through tentacle contact. Tentacle attack is usually seen through the development of sweeper tentacles where the tip is enriched in nematocyst and other toxins, as documented for Galaxea (Yosef et al, 2020) but this strategy has neither been registered for Porites nor was it observed in this experiment. Another possibility is that these proteins could be secreted into the surrounded water and reach a competitor via diffusion through the water column.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Another working hypothesis is that these candidate toxins could reach the competitor through tentacle contact. Tentacle attack is usually seen through the development of sweeper tentacles where the tip is enriched in nematocyst and other toxins, as documented for Galaxea (Yosef et al, 2020) but this strategy has neither been registered for Porites nor was it observed in this experiment. Another possibility is that these proteins could be secreted into the surrounded water and reach a competitor via diffusion through the water column.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, most field surveys and experiments to date have relied on visible signs to detect competitive interactions and determine their order of dominance. Visible competitive strategies of corals include: overtopping to starve competitors of light; deployment of mesenteric filaments to externally digest a competitor; and elongation of polyps or development of sweeper tentacles to enable contact followed nematocyst discharge [reviewed by Lang and Chornesky, 1990;Chadwick and Morrow, 2011;Yosef et al, 2020). Although these physical signs are reliable indicators of competition when competitors are in contact, it is now clear that a wide range of reef taxa including scleractinian corals, octocorals, sponges, and algae (Coll and Sammarco, 1983;Sammarco et al, 1983;Fearon and Cameron, 1996;Koh and Sweatman, 2000;Chadwick and Morrow, 2011) all produce toxins that could mediate competitive interactions without close contact.…”
Section: Introductionmentioning
confidence: 99%
“…More toxin-like transcripts were differentially expressed between endocoelic tentacles and nematospheres (15) than between endocoelic tentacles and exocoelic tentacles (13). Overall, the highest number of differentially expressed toxin-like transcripts was observed when comparing the body column and nematospheres (24), and the lowest when comparing exocoelic tentacles and nematospheres (1).…”
Section: Tissue-specific Expression Of Toxin-like Transcriptsmentioning
confidence: 93%
“…Both catch and sweeper tentacles are specialised for agonistic encounters with competitors, causing necrosis in other polyps, and are morphologically distinct from feeding tentacles [20,22,23]. A recent investigation of gene expression in sweeper and feeding tentacles in the stony coral Galaxea fasicularis revealed that toxin genes are differentially expressed across the two tentacle subsets [24] indicating that venom composition may vary across tentacle types when they fulfil distinct ecological functions. We surmised that toxin expression might similarly differ in a tentacle-specific manner in sea anemones, given that they also possess functionally distinct tentacle subsets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation